2013
DOI: 10.1073/pnas.1222534110
|View full text |Cite|
|
Sign up to set email alerts
|

Deciphering the rules by which 5′-UTR sequences affect protein expression in yeast

Abstract: The 5′-untranslated region (5′-UTR) of mRNAs contains elements that affect expression, yet the rules by which these regions exert their effect are poorly understood. Here, we studied the impact of 5′-UTR sequences on protein levels in yeast, by constructing a large-scale library of mutants that differ only in the 10 bp preceding the translational start site of a fluorescent reporter. Using a high-throughput sequencing strategy, we obtained highly accurate measurements of protein abundance for over 2,000 unique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
297
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(327 citation statements)
references
References 74 publications
29
297
1
Order By: Relevance
“…An alternative approach to the modeling of endogenous sequence is to use large-scale synthetic libraries (Dvir et al 2013;Shalem et al 2015;Wissink et al 2016). Although very powerful to dissect known cis-regulatory elements or to investigate small variations around select genes, the sequence space is so large that these large-scale perturbation screens cannot uncover all regulatory motifs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach to the modeling of endogenous sequence is to use large-scale synthetic libraries (Dvir et al 2013;Shalem et al 2015;Wissink et al 2016). Although very powerful to dissect known cis-regulatory elements or to investigate small variations around select genes, the sequence space is so large that these large-scale perturbation screens cannot uncover all regulatory motifs.…”
Section: Discussionmentioning
confidence: 99%
“…One of the interesting sequence elements that we found associated with half-life but did not turn out significant in the joint model is the start codon context. Given its established effect on translation initiation (Kozak 1986;Dvir et al 2013), the general coupling between translation and mRNA degradation (Roy and Jacobson 2013;Huch and Nissan 2014;, as well as several observations directly on mRNA stability for single genes (LaGrandeur and Parker 1999;Schwartz and Parker 1999), the start codon context may nonetheless functionally affect mRNA stability. Consistent with this hypothesis, large-scale experiments that perturb 5 ′ sequence secondary structure and start codon context indeed showed a wide range of mRNA level changes in the direction that we would predict (Dvir et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in studies of start codon context in derivatives of the CYC1 gene, Baim and Sherman (1988) found that U or C at the 23 position resulted in roughly a twofold increase in leaky scanning as compared to when a purine was at this position. Finally, based on a high throughput screen of start codon context nucleotides, Dvir et al (2013) reported a significant, but modest (,30%), impact of a 23 purine on reporter gene expression. At odds with these studies, flanking nucleotides have been shown to be important in selection of the non-AUG start codon on the GRS1 mRNA (Chen et al 2008) as well as in the selection of alternate AUG start codons on the MOD5 and CCA1 mRNAs (Werner et al 1987;Slusher et al 1991;Wolfe et al 1994).…”
Section: Mrna Features In Translation Initiationmentioning
confidence: 99%
“…In contrast, in yeast, the secondary structure of the 5 ′ UTR close to the start codon is selectively loose (Ringnér and Krogh 2005). Mutagenesis studies in both yeast (Dvir et al 2013) and Arabidopsis thaliana (Kim et al 2014) demonstrated that the local RNA secondary structure immediately upstream of the start codon plays a crucial role in determining translational efficiency and thus affects protein production.…”
Section: Thementioning
confidence: 99%